O patriotyzmie Wielkopolskim – ze spuścizny regionalizmu wielkopolskiego XIX/XX wieku - Kowalczyk, Ryszard (Wydawnictwo Nakowe WNPiD UAM w Poznaniu, 2019)
Autor skupił się na próbie zdefiniowania idei patriotyzmu wielkopolskiego, korzystając z dorobku nauki, literatury i czasopiśmiennictwa XIX/XX wieku, głównie z Wielkopolski. Osadził pojęcie patriotyzmu Wielkopolan na tle idei regionalizmu, w szczególności regionalizmu wielkopolskiego, którego podstawy programowe i praktyka w warunkach zaboru pruskiego były specyficzne dla tego regionu.

The author focuses on an attempt to define the idea of the patriotism of Wielkopolska, referring to the achievements of academia, literature and periodicals of the nineteenth/twentieth centuries, mainly from the region of Wielkopolska. He embeds the concept of the patriotism of the inhabitants of Wielkopolska in the concept of regionalism, in particular Wielkopolska regionalism, whose programmatic foundations and practice under Prussian partition were specific to this region.
On the patriotism of Wielkopolska – the heritage of regionalism in Wielkopolska in the nineteenth and twentieth centuries
Keywords: patriotyzm; regionalizm; Wielkopolska; zabór pruski; patriotism; regionalism; Wielkopolska region; Prussian partition